Composite chemical blocking gel material for preventing spontaneous combustion of coal in goaf and preparation method thereof

By developing a composite resistive leak plug gel material, combined with technical means such as physical crosslinked gel and nanomaterials, the problems of low retardation efficiency of coal spontaneous flame retardation and insufficient performance of leak plug materials in the existing technology are solved, and the effects of full-process resistive and leak plug air are achieved, which is suitable for fire prevention and control of coal mines.

CN118359766BActive Publication Date: 2025-04-04UNIV OF SCI & TECH BEIJING
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410409838.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-07
Publication Date
2025-04-04
Estimated Expiration
2044-04-07

AI Technical Summary

Technical Problem

In the prevention and control of the spontaneous combustion of goaf coal, the resistance time is short, the efficiency is low, the efficiency is easy to fail, the mechanical properties are poor, and the resistance characteristics of the leakage plugging material are insufficient, the fluidity is poor, and the high temperature is easy to fail, making it difficult to effectively solve the spontaneous combustion of goaf coal caused by air leakage.

Method used

A composite barrier-blocking gel material is developed to prepare gel materials with high water retention, thermal stability and chemical barrier properties through the combination of physical crosslinking gels, initiators, nanomaterials, toughening agents, crosslinking agents, flame retardants, chemical barriers and deionized water, and enhance the leakage barrier-blocking air capability through nanotroubleshooting materials.

Benefits of technology

The full-process resistance effect is achieved, the ability to plug leakage air is enhanced, the oxidation process of coal spontaneous combustion is delayed, the occurrence of coal spontaneous combustion is suppressed, and the toughness and coverage of materials are improved. It is suitable for fire prevention and control of coal mines and leakage air is controlled.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118359766B_ABST
    Figure CN118359766B_ABST
Patent Text Reader

Abstract

The present invention provides a composite retardant and plugging gel material for preventing and controlling spontaneous combustion of coal in goaf and a preparation method thereof, and belongs to the technical field of spontaneous combustion prevention and plugging of wind in coal mines. The material is made of a physical cross-linked gel, an initiator, a nano material, a toughening agent, a cross-linking agent, a flame retardant and a chemical inhibitor. First, the nano material is dripped into the physical cross-linked gel, the toughening agent is added to the solution, and after constant temperature stirring, the flame retardant and the cross-linking agent are added to the solution, and after constant temperature stirring, the initiator and the chemical inhibitor are added to the solution, and the constant temperature stirring is continued. Finally, the solution is freeze-dried and ground to obtain a composite retardant and plugging gel powder. The gel material in the material can quickly and firmly cover the surface of the coal body, preventing air from flowing in and contacting the coal body. In the process of gel flow, the air leakage zone in the goaf can be blocked, the oxygen concentration can be reduced, and the spontaneous combustion of coal can be fully inhibited. It is an efficient, environmentally friendly and stable inhibitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coal mine spontaneous combustion prevention and control and air leakage plugging, and in particular to a composite retardant and leakage plugging gel material for preventing spontaneous combustion of coal in goaf areas and a preparation method thereof. Background Art

[0002] Spontaneous combustion of coal may lead to safety accidents such as fire and explosion, causing serious casualties and property losses. In addition, spontaneous combustion of coal will also lead to the loss and waste of coal resources, affecting energy supply and energy security. In recent years, the development of coal spontaneous combustion inhibition and control technology has made great progress, including inert gas, three foams, inhibitors, etc. With the popularization of green and low-carbon concepts, the research on eco-friendly inhibitor gel has also made great progress. One of the most effective methods is to inject gel into the well. At present, inhibitor gel still has problems such as short inhibition time, low efficiency, easy failure, and poor mechanical properties. Filling and plugging technology can effectively block the leakage channel and reduce the contact between oxygen and coal seam. In recent years, scholars have combined inhibitor gel with plugging technology to develop products such as gel foam, plugging gel, and solidified gel foam, which has promoted the development of inhibitor technology for spontaneous combustion of coal in goaf. However, plugging materials also have the characteristics of insufficient inhibition properties, poor fluidity, and easy failure at high temperature. The existing technology has achieved certain effects in inhibiting spontaneous combustion of coal in goafs, but it cannot effectively solve the problem of spontaneous combustion of coal in goafs caused by air leakage, and further optimization is needed.

[0003] According to previous studies, dopamine hydrochloride has a molecular structure similar to mussel adhesive protein and can adhere to a variety of surfaces. Polyacrylamide has good water solubility and high chemical activity, and can easily obtain branched or network structures through grafting or cross-linking. The highly active aromatic hydroxyl groups in lignin have antioxidant activity. Phytic acid can produce compounds such as phosphoric acid and pyrophosphate during combustion and decomposition, which can easily capture free radicals and catalyze carbonization, and has excellent flame retardant properties.

[0004] Therefore, it is of great practical significance to develop a highly efficient, environmentally friendly, high-strength and full-process inhibitory plugging gel for different stages of coal spontaneous combustion. Summary of the invention

[0005] The present invention provides a composite barrier gel material for preventing and controlling spontaneous combustion of coal in goafs and a preparation method thereof. The gel material has high water retention and is not easy to dry and crack. It has high thermal stability and excellent chemical barrier performance, and can be fully barriered from the entire stage of coal spontaneous combustion. After adding nano-toughening materials, the gel's ability to plug wind leaks is enhanced, and it can coat cracks on the surface of coal to play an oxygen-isolating role. At the same time, the gel material selection is environmentally friendly, the production conditions are simple, and the effect is highly efficient. It can delay the spontaneous combustion and oxidation process of coal and inhibit the occurrence of coal spontaneous combustion.

[0006] In order to solve the above-mentioned invention object, the technical solution provided by the present invention is as follows:

[0007] A composite chemical blocking gel material for preventing spontaneous combustion of coal in goaf is prepared from physical cross-linking gel, initiator, nano material, toughening agent, cross-linking agent, flame retardant, chemical inhibitor and deionized water, wherein, by weight percentage, the physical cross-linking gel is 4.2-4.6%, the initiator is 0.3-0.5%, the nano material is 0.05-0.15%, the toughening agent is 2.1-2.3%, the cross-linking agent is 1.2-1.6%, the flame retardant is 2-2.4%, the chemical inhibitor is 0.2-0.6%, and the deionized water is the balance.

[0008] The physical cross-linked gel is formed by polymerization of polyacrylamide (PAM) and dopamine hydrochloride (PDA), wherein the mass ratio of polyacrylamide to dopamine hydrochloride is 1:0.4-0.5.

[0009] The flame retardant is a composite of sodium lignin sulfonate (LS) and phytic acid (PA), wherein the mass ratio of sodium lignin sulfonate to phytic acid is 1:1.6-2; the specific preparation process is as follows:

[0010] The method is prepared by adding sodium lignin sulfonate and 70% phytic acid solution into 60-70° C. deionized water, and then adding an initiator to react for 3-4 hours, wherein the mass ratio of initiator: (sodium lignin sulfonate + phytic acid) is 1:7-9.

[0011] The initiator is ammonium persulfate (APS); the nanomaterial is carbon nanofibers (CNFs); the toughening agent is 2-acrylamido-2-methylpropanesulfonic acid (AMPS); the crosslinking agent is methylenebisacrylamide (BIS); and the chemical inhibitor is epigallocatechin gallate (EGCG).

[0012] The preparation method of the composite blocking gel material comprises the following steps:

[0013] S1. Drop the nanomaterial suspension into the physically cross-linked gel to obtain a solution, then add the toughening agent into the solution, seal and magnetically stir in a constant temperature water bath for 2-3 hours to obtain a gel solution A;

[0014] S2, adding the flame retardant and the cross-linking agent to the gel solution, sealing and magnetically stirring for 3-4 hours in a constant temperature water bath to obtain a gel solution B;

[0015] S3, adding the initiator and the chemical inhibitor into deionized water, mixing and dissolving, adding the mixture into the gel solution B obtained in step S2, sealing and magnetically stirring in a constant temperature water bath for 3-4 hours, to obtain a gel solution C;

[0016] S4. The gel solution C prepared in S3 is placed at -50°C to -40°C for freeze-drying for 10-12 hours, and then ground to obtain a composite blocking gel material powder.

[0017] The preparation process of the nanomaterial suspension in step S1 is as follows:

[0018] Disperse dopamine hydrochloride and carbon nanofibers in deionized water at a mass ratio of 1:1, stir magnetically for 1-2 hours at room temperature, and then place in an ultrasonic cleaner for ultrasonic dispersion for 5-6 hours to obtain a suspension with a concentration of 3-3.5wt%;

[0019] The physical cross-linking gel preparation process is as follows:

[0020] The pH value of deionized water is adjusted to 8.5-9.5 with a 10% sodium hydroxide solution, polyacrylamide is added to the deionized water, and the reaction is continued with stirring for 20-30 minutes, and dopamine hydrochloride powder is added to the pre-polymerized polyacrylamide colloidal solution, and an initiator is added at the same time, and the polymerized solution is subjected to magnetic stirring for 20-30 minutes to obtain a physically cross-linked gel. In which, by mass ratio, the initiator: (polyacrylamide + dopamine hydrochloride) = 1:10-14.

[0021] In step S3, the mass ratio of the initiator to the chemical inhibitor is 1:1-1.2.

[0022] The temperature of the above-mentioned constant temperature water bath is 55°C-65°C.

[0023] Compared with the prior art, the above technical solution has at least the following beneficial effects:

[0024] In the above scheme, the composite leak-proofing gel has the moisturizing and coating effects of the multi-dimensional cross-linked gel, the chemical inhibitory effects of the sodium lignin sulfonate and phytic acid composite system and epigallocatechin gallate, and the sealing and oxygen isolation effects of the CNFs toughness enhancement, which can achieve the leak-proofing and inhibitory functions.

[0025] In the present invention, the multi-dimensional cross-linked structure enables it to have excellent mechanical properties, high strength, high toughness and high tensile resistance. After the gel flows to the surface of the coal, it can quickly and firmly cover the surface of the coal body, and penetrate into the gaps in the coal body to prevent air from flowing into and contacting the coal body. In addition, the gel has excellent wear resistance and corrosion resistance, so that it can maintain excellent performance in various harsh environments. Lignin-based flame retardants also have high carbonization properties and play a flame retardant role on multiple levels. Phytic acid can produce compounds such as phosphoric acid and pyrophosphate during combustion and decomposition, which are easy to capture free radicals and catalyze carbonization, and have excellent flame retardant properties. EGCG can effectively reduce the free hydroxyl groups of active groups in coal, while inhibiting the consumption of fatty groups in coal and slowing down the generation of carbonyl groups. Nanocarbon fibers can improve the tensile strength, impact strength and modulus of the matrix. During the flow of the gel, the air leakage zone in the goaf can be blocked, the oxygen concentration can be reduced, and the spontaneous combustion of coal can be avoided.

[0026] The present invention gives full play to the application of environmentally friendly materials in coal spontaneous combustion prevention and control projects, improves the toughness of materials, enhances coverage, and provides a new method and idea for coal mine fire prevention and control and plugging of air leakage management in my country. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 This is a flow chart of the preparation method of the composite retardant plugging gel material for preventing spontaneous combustion of coal in goaf areas of the present invention;

[0029] Figure 2 IR spectra of three gels used in the examples of the present invention;

[0030] Figure 3 The microscopic SEM images of four kinds of inhibited coal samples used in the embodiments of the present invention are shown in FIG. Figure 3 (a) is the SEM image of the raw coal sample. Figure 3 (b) is the SEM image of raw coal and PAM / PDA gel. Figure 3 (c) is the SEM image of raw coal and CNFs-PAM / PDA / AMPS gel. Figure 3 (d) is the SEM image of raw coal and CNFs-PAM / PDA-LS / PA / EGCG gel;

[0031] FIG4 is a TG / DTG-DSC curve diagram of four types of inhibited coal samples used in the embodiments of the present invention, wherein FIG4(a) is a graph of a raw coal sample, FIG4(b) is a graph of a raw coal sample and a PAM / PDA gel, FIG4(c) is a graph of a raw coal sample and a CNFs-PAM / PDA / AMPS gel, and FIG4(d) is a graph of a raw coal sample and a CNFs-PAM / PDA-LS / PA / EGCG gel;

[0032] Figure 5 It is a diagram of a plugging air pressure test chamber and a plugging air performance test experimental device in an embodiment of the present invention;

[0033] Figure 6 This is a curve diagram of the air leakage plugging performance of CNFs-PAM / PDA-LS / PA / EGCG gel in an embodiment of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0036] The invention provides a composite chemical blocking gel material for preventing and controlling spontaneous combustion of coal in goaf areas and a preparation method thereof.

[0037] The composite blocking and leak-proof gel material is prepared from physically cross-linked gel, initiator, nano material, toughening agent, cross-linking agent, flame retardant, chemical inhibitor and deionized water, wherein, by weight percentage, the physically cross-linked gel is 4.2-4.6%, the initiator is 0.3-0.5%, the nano material is 0.05-0.15%, the toughening agent is 2.1-2.3%, the cross-linking agent is 1.2-1.6%, the flame retardant is 2-2.4%, the chemical inhibitor is 0.2-0.6%, and the deionized water is the balance.

[0038] like Figure 1 As shown, the preparation method of the composite blocking gel material comprises the following steps:

[0039] S1. Drop the nanomaterial suspension into the physically cross-linked gel to obtain a solution, then add the toughening agent into the solution, seal and magnetically stir in a constant temperature water bath for 2-3 hours to obtain a gel solution A;

[0040] S2, adding the flame retardant and the cross-linking agent to the gel solution, sealing and magnetically stirring for 3-4 hours in a constant temperature water bath to obtain a gel solution B;

[0041] S3, adding the initiator and the chemical inhibitor into deionized water, mixing and dissolving, adding the mixture into the gel solution B obtained in step S2, sealing and magnetically stirring in a constant temperature water bath for 3-4 hours, to obtain a gel solution C;

[0042] S4. The gel solution C prepared in S3 is placed at -50°C to -40°C for freeze-drying for 10-12 hours, and then ground to obtain a composite blocking gel material powder.

[0043] This will be described below with reference to specific embodiments.

[0044] Example 1

[0045] Take 100 ml of deionized water in a beaker and place it in a magnetic stirring water bath at 60°C for preheating. Use a 10% NaOH solution to adjust the pH to 9. Weigh 3 g of polyacrylamide and add it to the beaker. Continue stirring and reacting for 30 minutes to allow it to fully polymerize and form a uniform colloid. Weigh 1.4 g of dopamine hydrochloride powder and add it to the prepolymerized PAM colloid. At the same time, add 0.4 g of initiator ammonium persulfate powder to the beaker and polymerize with magnetic stirring for 15 minutes until it becomes a stable deep red color. Seal the polymerization reaction for 3 hours to obtain PAM / PDA gel.

[0046] PDA and CNFs were dispersed in deionized water, magnetically stirred for 2 hours at room temperature, and then placed in an ultrasonic cleaner for ultrasonic dispersion for 5 hours to obtain a suspension with a PDA-CNFs concentration of 3.5wt%. PDA-CNFs suspension was dripped into the PAM / PDA gel solution, and the sealing reaction was carried out for 3 hours. 2.7g AMPS was weighed and added to the gel solution after polymerization and cross-linking, and stirred at 60°C for 2 hours to obtain a CNFs-PAM / PDA / AMPS gel solution.

[0047] 1.4g LS and 1ml phytic acid solution were added to deionized water, and the initiator was added to react for 2h, then added to the gel solution, and the crosslinker BIS was added. After sealing and polymerization for 3h, a high-strength gel solution was obtained by reacting for 3h. 0.05g EGCG powder was taken, dissolved in an appropriate amount of deionized water, and the initiator potassium persulfate was added. The pretreated EGCG solution was slowly dripped into the gel solution with a rubber-tipped dropper, and the colloid was uniform after continuous stirring and sealing polymerization for 3h. The gel solution was placed in a freeze dryer, freeze-dried at -50℃ for 12h, and then ground to obtain CNFs / PAM / PDA / LS-EGCG / PA gel powder.

[0048] Example 2

[0049] Take 100 ml of deionized water in a beaker and place it in a magnetic stirring water bath at 65°C for preheating. Use a 10% NaOH solution to adjust the pH to 10. Weigh 3.2 g of polyacrylamide and add it to the beaker. Continue stirring and reacting for 30 minutes to allow it to fully polymerize and form a uniform colloid. Weigh 1.5 g of dopamine hydrochloride powder and add it to the prepolymerized PAM colloid. At the same time, add 0.42 g of initiator ammonium persulfate powder to the beaker and stir magnetically to polymerize until it presents a stable deep red color. Seal the polymerization reaction for 4 hours to obtain PAM / PDA gel.

[0050] PDA and CNFs were dispersed in deionized water, magnetically stirred for 3 hours at room temperature, and then ultrasonically dispersed in an ultrasonic cleaner for 5.5 hours to obtain a suspension with a PDA-CNFs concentration of 3.8wt%. PDA-CNFs suspension was dripped into the PAM / PDA gel solution, and the sealing reaction was carried out for 3 hours. 2.5g AMPS was weighed and added to the gel solution after polymerization and cross-linking, and stirred at 65°C for 3 hours to obtain a CNFs-PAM / PDA / AMPS gel solution.

[0051] 1.2g LS and 1.2ml phytic acid solution were added to deionized water, and the initiator was added to react for 2.5h, then added to the gel solution, and the crosslinker BIS was added. After sealing and polymerization for 3.5h, the high-strength gel solution was obtained by reacting for 3.5h. 0.06g EGCG powder was taken, dissolved in an appropriate amount of deionized water, and the initiator potassium persulfate was added. The EGCG was fully stirred to induce a free radical reaction in EGCG. The pretreated EGCG solution was slowly dripped into the gel solution with a rubber-tipped dropper. After continuous stirring and sealing polymerization for 3.5h, the reaction was continued for 4h until the colloid was uniform. The gel solution was placed in a freeze dryer, freeze-dried at -40°C for 12h, and then ground to obtain CNFs / PAM / PDA / LS-EGCG / PA gel powder.

[0052] Test 1

[0053] Infrared spectroscopy experiments were performed on the three experimental samples of PAM / PDA, CNFs-PAM / PDA / AMPS and CNFs-PAM / PDA / LS-EGCG / PA obtained in Example 1.

[0054] The infrared spectrum of the samples was tested using a Nicolet iS50 Fourier transform infrared spectrometer. The scanning wave number was 400-4000cm -1 . Resolution is 4cm -1 , the number of scans is 64 times.

[0055] The infrared test results of the three samples are as follows: Figure 2As shown in the PAM / PDA / LS-EGCG / PA spectrum, it can be seen that at 3415cm -1 There is an obvious broad absorption band at 3266cm, which is due to the attribution peak of hydroxyl stretching vibration after adding sodium lignin sulfonate. -1 and 2930cm -1 The NH symmetric stretching vibration and -CH2 stretching vibration in polyacrylamide appeared respectively. -1 The strong peak that appears corresponds to the C=O vibration in the amide. -1 and 808cm -1 The peak at 1550-1382cm corresponds to the CN stretching vibration on the benzene ring, which indicates that the phenolic hydroxyl group on dopamine reacts with the -NH group of polyacrylamide to form a high molecular polymer. -1 There are a series of characteristic absorption peaks belonging to benzene rings, which gradually increase with the addition of LS, phytic acid and EGCG, proving that the additives are organically polymerized together. At the same time, the peaks at 1043cm-1 (PO bending vibration) and 985cm-1 (POC stretching vibration) can be attributed to the introduction of phytic acid. The changes in these characteristic peaks prove that a reaction has occurred between phytic acid and the main body of the gel.

[0056] Test 2

[0057] The three experimental samples of PAM / PDA, CNFs-PAM / PDA / AMPS and CNFs-PAM / PDA / LS-EGCG / PA obtained in Example 1 were subjected to scanning electron microscopy testing after heating.

[0058] The experiment used a German ZEISS GeminiSEM 300 scanning electron microscope. The raw coal samples and the inhibited coal samples were placed in a heating furnace and heated to 300°C at a heating rate of 5°C / min. The morphology of the surface carbon layer in the raw coal and inhibited coal samples after heating was observed using a scanning electron microscope.

[0059] The microscopic morphology of the coal sample and the retardant coal sample after being heated to 300℃ in a heating furnace is shown in the figure. Figure 3 As shown. Figure 3 As can be seen in (a), the coal is in a loose state after thermal heating, and the coal ash is mostly dispersed around the coal block. After heating, more cracks and holes appear on the surface of the coal, which increases the contact area between the coal surface and the air, making the coal more susceptible to coal-oxygen complex reaction. Figure 3 (b) It can be seen that the addition of gel greatly reduces the degree of surface fragmentation of the coal sample, and it is less likely to burn than the original coal after heating. Figure 3(c) and (d) show that with the addition of nanocarbon fibers, the mechanical properties of the gel are enhanced, the grooves on the surface of the coal sample are reduced after heating, and the thickness of the carbon layer increases, which is not conducive to the discharge of heat and oxygen from the coal pores. With the deepening of the cross-linking degree of the inhibitor gel and the addition of chemical inhibitors, the block shape of the coal surface becomes more and more complete. In particular, it can be seen from (d) that the surrounding coal ash content is reduced and the coal block shape is larger. Due to the synergistic inhibitory effect of sodium lignin sulfonate, oxalic acid and EGCG, the expanded carbon layer wraps the surface of the coal seam to form a uniform carbon block, which effectively reduces the area of ​​coal exposed to the air. The expanded gel forms a carbon layer with the coal surface, which can effectively isolate heat, flames and combustible gases. Therefore, CNFs-PAM / PDA-LS / PA / EGCG has the best inhibitory performance and sealing effect.

[0060] Test 3

[0061] The three experimental samples of PAM / PDA, CNFs-PAM / PDA / AMPS and CNFs-PAM / PDA / LS-EGCG / PA obtained in Example 1 were subjected to thermogravimetric and DSC analysis.

[0062] The experiment used STA7200 thermogravimetric analyzer and SDT Q600 thermal tester. The sample amount was 10 mg, and an alumina crucible was used. The air flow was set to 50 ml / min, the heating rate was 5 °C / min, and the heating range was 20-600 °C. The TG / DTG-DSC curves of each sample were measured to evaluate the inhibitory effect of the inhibitory gel.

[0063] According to the changing trend of the curve, the oxidative spontaneous combustion reaction process of the four groups of samples is divided into four stages: evaporation and adsorption, oxygen absorption and weight gain, thermal decomposition and combustion, and burnout. As shown in Figure 4, after adding the inhibitor gel, the TG curve is delayed compared with the raw coal in the evaporation and adsorption stages. The temperature in this stage is low, and it is mainly physical reaction. The gas in the raw coal gradually begins to desorb, and the coal sample shows a continuous weight loss state. Among them, the sample with the addition of CNFs-PAM / PDA-LS / PA / EGCG inhibitor gel has the longest extension, about 17.5%. This is because the moisture in the coal and the barrier sample begins to evaporate at the beginning, and the adsorbed gas gradually desorbs. And with its good moisture retention, it has a significant inhibitory effect on the low temperature stage of coal spontaneous combustion.

[0064] During the oxygen absorption and weight gain stage, a large number of aromatic structures in the coal sample will break bonds, causing the structures with strong oxygen affinity to increase rapidly, and the chemical reaction begins to intensify at this time. As shown in Figure 4, after the addition of PAM / PDA gel, the inhibitory gel has a significant delaying effect on this stage, and the end temperature is delayed from 227.51°C to 251.76°C, a delay of 10.6%. After the addition of CNFs, the inhibitory gel and PDA / PAM have similar effects on the end temperature of this stage. This is because CNFs have obvious thermal insulation effects and high stability in the high temperature stage, and the inhibitory effect is not obvious in the low temperature stage. The CNFs-PAM / PDA-LS / PA / EGCG inhibitory gel delays this stage by about 20%. This is because LS and PA react quickly with the active groups in the broken aromatic rings to generate stable intermediates that are not easy to decompose, cutting off the chain reaction.

[0065] During the thermal decomposition and combustion stages, high-temperature oxidation proceeds rapidly. The aromatic structure undergoes comprehensive cracking. The violent oxidation reaction causes a significant reduction in the weight of the coal sample. After the water-retaining gel component in the CNFs-PAM / PDA-LS / PA / EGCG inhibitor gel fails, the grafted EGCG plays a chemical inhibitory role in passivating active groups and scavenging free radicals in the high-temperature stage. The continuous temperature was shortened from 281.33°C to 261.26°C. The moisturizing and covering effects of the three-dimensional gel in the low-temperature stage, the chain reaction cutting effect of LS and PA in the heating stage, and the inhibitory effect of the nano-inhibiting material CNFs and the chemical inhibitor EGCG in the high-temperature stage achieve an overall gain effect on the inhibitory system, greatly inhibiting the process of coal spontaneous combustion.

[0066] At the same time, it can be seen from Figure 4 that the temperature point with the lowest value on the DTG curve is gradually delayed, which means that after the inhibition, the most intense combustion moment of the coal sample is delayed. The process of coal spontaneous combustion is continuously delayed. And from the DSC curve, it can be seen that the position of the highest exothermic peak of CNFs-PAM / PDA-LS / PA / EGCG inhibition gel increased from 451.65℃ to 471.12℃. The average heat release in the exothermic stage decreased from 8910J / g to 7027J / g, a decrease of about 26.8%. It can be seen that the CNFs-PAM / PDA-LS / PA / EGCG inhibition gel improves the skeleton stability and mechanical properties, can better wrap the coal seam surface, and the inhibition means are diverse and effective, which enhances the inhibition ability from the whole process of coal spontaneous combustion.

[0067] Test 4

[0068] The three experimental samples of PAM / PDA, CNFs-PAM / PDA / AMPS and CNFs-PAM / PDA / LS-EGCG / PA obtained in Example 1 were subjected to air leakage plugging experimental analysis.

[0069] Plugging air pressure test chamber and plugging air performance test experimental device such as Figure 5 As shown. The coal sample was crushed with a jaw crusher, and coal blocks with a diameter of about 1.5 cm were selected. The coal blocks were placed in the test chamber, and the sample area was filled to a height of 15 cm (about 700 mL of coal was actually used), and about 300 mL of the inhibitor gel solution was poured in, and the gap of the test chamber cover was sealed with hot melt adhesive.

[0070] Through the air leakage performance experiment, the curves of the outlet pressure and pressure difference of CNFs-PAM / PDA-LS / PA / EGCG gel changing with the inlet pressure were obtained. Figure 6 . When the outlet pressure of the plugging sample is lower than 1.27 kPa, the outlet pressure is always 0, indicating that the gel effectively prevents airflow from penetrating under this pressure. When the air pressure reaches 1.27 kPa, the gel suffers certain damage under high air pressure and begins to leak (hereinafter we refer to the inlet pressure at this time as the limiting air pressure), and the outlet pressure rises accordingly until it reaches 2.6 kPa and becomes consistent with the inlet pressure. CNFs-PAM / PDA-LS / PA / EGCG forms a tough gel structure through sufficient cross-linking, which improves the overall strength of the gel. Although the pressure difference continues to decrease after reaching the limiting air pressure, it remains not less than 0 until 2.53 kPa. This shows that the gel has certain compressive and tensile properties, and only part of the structure is damaged under high air pressure, and the remaining structure can still effectively hinder airflow. Therefore, CNFs-PAM / PDA-LS / PA / EGCG gel performs excellently in plugging air leakage performance and can meet the needs of plugging air leakage in coal mines.

[0071] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. The protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A composite anti-leakage gel material for preventing spontaneous combustion of coal in goaf, characterized in that: The invention is prepared from a physical cross-linking gel, an initiator, a nano material, a toughening agent, a cross-linking agent, a flame retardant, a chemical inhibitor and deionized water, wherein, by weight percentage, the physical cross-linking gel is 4.2-4.6%, the initiator is 0.3-0.5%, the nano material is 0.05-0.15%, the toughening agent is 2.1-2.3%, the cross-linking agent is 1.2-1.6%, the flame retardant is 2-2.4%, the chemical inhibitor is 0.2-0.6%, and the balance is deionized water; The physically cross-linked gel is formed by polymerization of polyacrylamide and dopamine hydrochloride, wherein the mass ratio of polyacrylamide to dopamine hydrochloride is 1:0.4-0.5; The flame retardant is a composite of sodium lignin sulfonate and phytic acid, wherein the mass ratio of sodium lignin sulfonate to phytic acid is 1:1.6-2; the specific preparation process is as follows: The sodium lignin sulfonate and phytic acid solution with a concentration of 70% are added to deionized water at 60°C-70°C, and then an initiator is added to react for 3-4 hours to obtain the product, wherein the mass ratio of initiator: sodium lignin sulfonate + phytic acid is 1:7-9; The initiator is ammonium persulfate; the nano material is nano carbon fiber; the toughening agent is 2-acrylamido-2-methylpropane sulfonic acid; the cross-linking agent is methylene bisacrylamide; and the chemical inhibitor is epigallocatechin gallate.

2. The method for preparing the composite retardant and plugging gel material for preventing spontaneous combustion of coal in goaf according to claim 1, characterized in that: The steps include: S1. Drop the nanomaterial suspension into the physically cross-linked gel to obtain a solution, then add the toughening agent into the solution, seal and magnetically stir in a constant temperature water bath for 2-3 hours to obtain a gel solution A; S2, adding the flame retardant and the cross-linking agent to the gel solution, sealing and magnetically stirring for 3-4 hours in a constant temperature water bath to obtain a gel solution B; S3, adding the initiator and the chemical inhibitor into deionized water, mixing and dissolving, adding the mixture into the gel solution B obtained in step S2, sealing and magnetically stirring in a constant temperature water bath for 3-4 hours, to obtain a gel solution C; S4. The gel solution C prepared in S3 is placed at -50°C to -40°C for freeze-drying for 10-12 hours, and then ground to obtain a composite blocking gel material powder.

3. The method for preparing the composite retardant and plugging gel material for preventing spontaneous combustion of coal in goaf according to claim 2, characterized in that: The nanomaterial suspension preparation process in step S1 is as follows: Disperse dopamine hydrochloride and carbon nanofibers in deionized water at a mass ratio of 1:1, stir magnetically for 1-2 hours at room temperature, and then place in an ultrasonic cleaner for ultrasonic dispersion for 5-6 hours to obtain a suspension with a concentration of 3-3.5wt%; The physical cross-linking gel preparation process is as follows: The pH value of deionized water is adjusted to 8.5-9.5 with a 10% sodium hydroxide solution, polyacrylamide is added to the deionized water, and the reaction is continued with stirring for 20-30 minutes, dopamine hydrochloride powder is added to the pre-polymerized polyacrylamide colloid solution, an initiator is added at the same time, and the polymerization is carried out with magnetic stirring for 20-30 minutes to obtain a physically cross-linked gel.

4. The method for preparing the composite retardant and plugging gel material for preventing spontaneous combustion of coal in goaf according to claim 3 is characterized in that: During the preparation of the physical cross-linked gel, the mass ratio of the initiator: polyacrylamide + dopamine hydrochloride is 1:10-14.

5. The method for preparing the composite retardant and plugging gel material for preventing spontaneous combustion of coal in goaf according to claim 2, characterized in that: In step S3, the mass ratio of the initiator to the chemical inhibitor is 1:1-1.

2.

6. The method for preparing the composite retardant and plugging gel material for preventing spontaneous combustion of coal in goaf according to claim 2, characterized in that: The constant temperature water bath temperature is 55°C-65°C.

Citation Information

Patent Citations

  • Preparation method of hydrogel-based composite inhibitor for coal mine

    CN114797693A

  • Double-grid gel composite inhibitor for inhibiting spontaneous combustion of coal and preparation method of double-grid gel composite inhibitor

    CN116478703A